Gattu lagā le peca - Shandilya, Sandesh (Eagle Home Entertainment, 2012)
In this town, the sky is full of kites, and all the kids are obsessed with kite-flying. The kite, Kali, rules the skies. No one knows who flies Kali. No one can defeat Kali. An illiterate street urchin takes up the challenge. With neither money nor education on his side, he sets out for his goal. Dreams aren't impossible when the desire is strong.